Scenario-based electronic learning: a viable educational method. - Ellis, Ricky; Collins, Niamh (Journal of Paramedic Practice, 2012)
All prehospital practitioners should participate in the task of establishing a body of knowledge that relates specifically to prehospital care (Gregory, 2011). The rapid pace of change in prehospital knowledge and the release of new clinical practice guidelines would indicate that systems need to be developed to disseminate this knowledge effectively and efficiently. Electronic learning (e-learning) is one method. Prehospital personnel's reaction to electronic learning has not been widely evaluated. Aims: this article presents an overview of the lessons learnt through a structured evaluation of a pilot e-learning module which was delivered to advanced paramedics. Methods: A series of scenario-based educational modules encompassing recent changes in advanced paramedic clinical practice guidelines were developed. In February 2011, the pilot module was made available to 207 advanced paramedics in Ireland. A quantitative and qualitative assessment of this programme was performed. Results: during a four-week trial period, 51 out of 64 registered advanced paramedics who participated in the e-Learning programme, completed an extensive evaluation of the pilot module. The results indicate a strong positive response towards e-learning as a method of delivering learning to advanced paramedics. Discussion: e-learning is a medium set to gain popularity as a method of training in the future due to the ability to rapidly transfer new and updated clinical knowledge within a cohort of practitioners. The medium offers flexibility and cost efficiencies. Conclusion: e-learning has proved a successful tool for delivery of prehospital educational information. Practitioners are prepared to take responsibility for their own education and appreciate the ability to schedule their own learning time.